Ultrafiltered pig leukocyte extract (IMUNOR) decreases nitric oxide formation and hematopoiesis-stimulating cytokine production in lipopolysaccharide-stimulated RAW 264.7 macrophages - Hofer, Michal; Vacek, Antonín; Lojek, Antonín; Holá, Jirina; Streitová, Denisa (International immunopharmacology, 2007)
A low-molecular-weight (<12 kDa) ultrafiltered pig leukocyte extract, IMUNOR, was tested in experiments in vitro on non-stimulated and lipopolysaccharide (LPS)-stimulated murine RAW 264.7 macrophages in order to assess modulation of nitric oxide (NO) production (measured indirectly as the concentration of nitrites), hematopoiesis-stimulating activity of the supernatant of the macrophage cells (ascertained by counting cell colonies growing from progenitor cells for granulocytes and macrophages (GM-CFC) in vitro), and the release of hematopoiesis-stimulating cytokines. No hematopoiesis-stimulating activity and cytokine or NO production were found in the supernatant of non-stimulated macrophages. It was found that IMUNOR does not influence this status. Supernatant of LPS-stimulated macrophages was characterized by hematopoiesis-stimulating activity, as well as by the presence of nitrites, interleukin-6 (IL-6), and granulocyte colony-stimulating factor (G-CSF). A key role in the hematopoiesis-stimulating activity of the supernatant of LPS-stimulated macrophages could be ascribed to G-CSF since the formation of the colonies could be abrogated nearly completely by monoclonal antibodies against G-CSF. IMUNOR was found to suppress all the mentioned manifestations of the LPS-activated macrophages. When considering these results together with those from our previous in vivo study revealing stimulatory effects of IMUNOR on radiation-suppressed hematopoiesis, a hypothesis may be formulated which postulates a homeostatic role of IMUNOR, consisting in stimulation of impaired immune and hematopoietic systems but also in cutting back the production of proinflammatory mediators in cases of overstimulation which threats with undesirable consequences.
Keywords: Tissue Extracts; lipopolysacharidy; Hematopoiesis; buněčné extrakty; cytokiny; Lipopolysaccharides; Female; makrofágy; oxid dusnatý; zvířata; Nitric Oxide; myši; Cells, Cultured; faktor stimulující kolonie granulocytů; Mice; Swine; buněčné linie; hematopoéza; tkáňové extrakty; imunologické faktory; ženské pohlaví; Cell Line; Cell Extracts; kultivované buňky; Cytokines; Granulocyte Colony-Stimulating Factor; Immunologic Factors; Bone Marrow Cells; Mice, Inbred Strains; Animals; Macrophages; inbrední kmeny myší; prasata; buňky kostní dřeně